Review of Islamic Education Management Research in Schools - Mualifah, Lisna; Warisno, Andi; Ansori, Afif; Andari, An An (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to describe and conclude the results of Islamic education management studies for the period 2015 to 2022. This is qualitative-library research. Researchers conducted research on the results of research in journals related to the management of Islamic education in schools/madrasas from 2015-2022. The data and research data sources are in the form of